Retrospective isotope monitoring reveals spatial and temporal effects of anthropogenic pressures on the trophic ecology of European wildcats (Felis silvestris) in Germany - Chris Baumann; Sabrina Streif; Ayenne S. Akarsu; Carsten Nowak; Dorothée G. Drucker (PLoS ONE, 2026)
The European wildcat ( Felis silvestris ) is increasingly exposed to anthropogenic pressures, including habitat fragmentation, agricultural intensification, road mortality and hybridisation with domestic cats ( Felis catus ). These factors may alter trophic behaviour, ecological roles, and long-term conservation prospects. In this study, we use stable isotope analysis of cat hair ( δ ¹³C, δ ¹⁵N, δ ³⁴S) to assess dietary patterns and niche dynamics in wildcats, domestic cats, and their hybrids across three German regions. We combine two complementary case studies: (1) a spatial comparison between a core population with low hybridisation rates (Taunus) and a heavily introgressed range edge population (Markgräflerland), and (2) a 26-year retrospective dataset from Thuringia (East Thuringia, Hainich, Harz Foreland, Thuringian Basin, Thuringian Forest) to analyse temporal dietary trends and responses to landscape change. Our results reveal trophic differences among the taxa. Wildcats showed the narrowest isotopic niches, particularly in the Taunus, indicating strong ecological specialization. In contrast, hybrids occupied the broadest niches and showed substantial isotopic overlap with wildcats, especially in the region with high hybridisation rates. Domestic cats exhibited minimal niche overlap with wildcats, suggesting limited trophic competition. Long-term trends in Thuringian wildcats revealed increasing δ ¹³C values over time, primarily in summer-grown hair, suggesting a growing reliance on prey associated with agricultural habitats. Correlations with land use and individual traits further highlighted how both factors shape isotopic signatures. Retrospective isotope monitoring using archived tissues provides a powerful, non-invasive tool to assess anthropogenic influences, hybridisation impacts, and long-term ecological change in elusive or protected carnivores such as the European wildcat.